Identification of Medicinally Active Ingredient in Ultradiluted Digitalis purpurea: Fluorescence Spectroscopic and Cyclic-Voltammetric Study - Anup Sharma; Bulbul Purkait (Journal of Analytical Methods in Chemistry)
Serially diluted and agitated (SAD) drugs available commercially are in use with great faith because of the astonishing results they produce. The scientific viewpoint attached to the centuries-old therapy with SAD drugs, as in homeopathy, remained doubtful for want of appropriate research and insufficient evidence base. The conflicting points related to SAD drug mostly related to the level of concentrations/dilutions, use of drug in contradictory clinical conditions compared to the modern system of medicine, identification of medicinally active ingredient in concentrations and dilutions used in commercially available SAD drugs, and lack of laboratory-based pharmacological data vis-à-vis modern medicine. Modus operandi of SAD drug is also unknown. To address some of these issues an analytical study was carried out wherein commercially available SAD drug Digitalis purpurea, commonly used in different systems of medicine, was put to test. Various concentrations of commercially available Digitalis purpurea were analyzed using analytical methods: cyclic voltammetry, emission spectroscopy, and UV-VIS spectroscopy. These analytical methods apparently identified the medicinal ingredients and effect of serial dilution in commercial preparation of the drugs.